Volatilization behavior of polycyclic aromatic hydrocarbons from the oil-based residues of shale drill cuttings. (February 2022) - Wang, Shu; Qin, Jihong; Xie, Bingxin; Sun, Hui; Li, Xin; Chen, Wenqing
Abstract: Shale gas, an emerging oil-bearing and pillar industry at home and abroad, has a very large impact on economic development and industry, but the resulting emerging pollutants pose a serious threat to the environment. Drilling cuttings, the primary byproduct of the exploration and mining of shale gas, are potentially hazardous types of waste that seriously deplete land resources and pose environmental safety problems. In this paper, a long-term static volatilization experiment was conducted to study the volatilization of polycyclic aromatic hydrocarbons (PAHs) in the oil-based residue of shale gas drill cuttings. Furthermore, the effects of some relevant environmental factors controlling the volatilization behavior were evaluated, including different particle sizes, temperatures and illuminances. The results showed that (1) the volatilization concentrations of PAHs gradually increased with prolonged volatilization time. PAHs with smaller ring numbers were present at the highest concentrations among the detected PAHs, and they were more readily volatilized and could be detected earlier. (2) The C-history method was found to significantly describe the kinetic process of the volatilization of PAHs. (3) Different environmental factors had different effects on the volatilization of PAHs. We found that increasing the temperature and illuminance and decreasing the particle size increased volatility. Through canonical correspondence analysis, PAHs volatilization was found to be a complex process, so volatilization tests under simulated environmental conditions are of scientific and environmental interest. Graphical abstract: Image 1 Highlights: The concentrations of PAHs gradually increased with prolonged volatilization time. The C-history method could fine describe PAHs volatilizing in oil-based cuttings. Different environmental factors had different impacts on the volatilization of PAHs.